Screening pasts for healthy futures: Egg donation and the making of the ‘healthy’ baby in Spanish fertility clinics - Laura Perler (Gender)
What kind of life is considered reproducible in a fertility clinic? What is the specific understanding of technology and progress and what does this have to do with the desirability of certain bodies? What does egg donation have to do with selection? These are the guiding questions of this article, in which I explore the idea of the ‘healthy’ baby in third-party reproduction in Spain. Based on my ethnographic fieldwork in a fertility clinic in Valencia, I analyse the clinical practices through which ‘healthy’ babies are produced. I argue that a technophilic and ableist vision of the future is at the centre of this idea of a ‘healthy’ child. Furthermore, I suggest that the use of genetic selection techniques is normalised through narratives of progress and that the power structures of a transnational bioeconomy are (re)produced as a result. Finally, I show that the practice of egg donation in Spain must be understood not only as assisted but also as selective reproduction.